2018
DOI: 10.1002/tox.22679
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic and morphological effects of microcystin‐LR, cylindrospermopsin, and their combinations on the human hepatic cell line HepG2

Abstract: Cylindrospermopsin (CYN) and Microcystin-LR (MC-LR) are toxins produced by different cyanobacterial species, which are found mainly in freshwater reservoirs. Both of them can induce, separately, toxic effects in humans and wildlife. However, little is known about the toxic effects of the combined exposure, which could likely happen, taking into account the concomitant occurrence of the producers. As both cyanotoxins are well known to induce hepatic damage, the human hepatocellular HepG2 cell line was selected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 75 publications
2
18
2
Order By: Relevance
“…Moreover, a risk assessment can be greatly influenced when diverging from individual toxin exposure to a multi-toxin exposure scenario. Gutiérrez-Praena et al [41] found an antagonistic effect of CYN and MC-LR when investigating the cytotoxicity of binary mixtures in comparison to the individual toxins in HepG2 cells. Hercog et al [42] observed a genotoxic potential of CYN/MC-LR mixtures comparable to that of CYN alone when using the micronucleus (MN) and comet assays in the same experimental model.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a risk assessment can be greatly influenced when diverging from individual toxin exposure to a multi-toxin exposure scenario. Gutiérrez-Praena et al [41] found an antagonistic effect of CYN and MC-LR when investigating the cytotoxicity of binary mixtures in comparison to the individual toxins in HepG2 cells. Hercog et al [42] observed a genotoxic potential of CYN/MC-LR mixtures comparable to that of CYN alone when using the micronucleus (MN) and comet assays in the same experimental model.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, two studies found no significant differences between the vehicle control and CYN-treated HepG2 cells at 0.5 μg/mL [ 28 ] and 2 μg/mL [ 29 ] after 24 h.…”
Section: Resultsmentioning
confidence: 99%
“…Although the simultaneous occurrence of cyanotoxins such as MCs and CYN is being reported more and more frequently [44,55], toxicological studies focusing on their potential interaction are very scarce [50,56]. Particularly, the genotoxicity of mixtures is of great interest for humans exposed to contaminated waters and food with cyanotoxins, due to the possible carcinogenic effects of MC-LR and pro-genotoxic activity of CYN.…”
Section: Discussionmentioning
confidence: 99%
“…Even though occurrence data show that MC-RR and other minority MCs are distributed worldwide becoming sometimes predominant, the congener MC-LR is widely distributed and the main focus of toxicological studies [8,64]. The ratio CYN/MC concentrations could oscillate between countries and continents, climatic conditions, or composition of the cyanobacteria communities [44,45], and in this study the ratio 1:10 CYN/MC-LR was chosen to compare or confirm previous toxicity studies in which combinations of CYN/MC-LR were assayed [49][50][51]. Furthermore, the International Conference on Harmonisation (ICH) S2 guidelines [90] and the OECD 474 [53] and OECD 489 [54] guidelines for the MN and Comet assay, respectively, recommend for the combined MN-comet assay the use of the highest dose and two additional lower doses [58] appropriately separated by less than √ 10 to prove dose-related responses [54].…”
Section: Experimental Design and Treatmentmentioning
confidence: 99%
See 1 more Smart Citation